Communist Movement on the Social Revolution at Pekalongan Residence in 1945 - Hakim, Muzaky Ulya; Faidi, Ahmad (Journal of Islamic History, 2023)
The social revolution in the Pekalongan Residency was an uprising that emerged as a response to the proclamation of Indonesia's independence. This revolution was marked by tension between revolutionary groups and pangreh praja officials, who were seen as representatives of the colonial system. In this context, the revolution was understood as an effort to transform the social order towards a more democratic system, with its key figures coming from Islamic, socialist, and communist circles.This research uses historical research methods, namely: Heuristic stages of collecting sources, verification or criticism of sources, Interpretation or interpretation, and historiography or historical writing. Then the use of data related to the theme raised is primary source data and secondary sources and the same literature. Data collection by researchers is carried out by literature studies and archival document studies. The study's findings show that the social revolution in the Pekalongan Residency was triggered by several main factors, namely the suffering and oppression experienced by the people during Dutch and Japanese colonialism, corruption and misconduct among pangreh praja officials (Regents, Wedana, District Chiefs, and Village Heads), and the silence of the pangreh praja regarding the proclamation news. This revolutionary event involved conflict, violence, the forced overthrow of pangreh praja officials, and the takeover of the Pekalongan Residency government by revolutionary groups. During these events, radical or communist groups had strong influence, acting as the main drivers of uprisings in various areas and determining the direction of the social revolution within the Pekalongan Residency. Keywords: influence, communist movement, social revolution, and pekalongan residency. REFERENCES Aman. 2015. Revolusi Sosial di Brebes. Yogyakarta: Penerbit Ombak. Alwijaya, Ahmad. 2023. TKR (Tentara Keamanan Rakyat) dan Resimen XVII Dalam Penyelesaian Gerakan Rakyat di Karesidenan Pekalongan Tahun 1945. Skripsi. Program Studi Sejarah Peradaban Islam, Fakultas Ushuluddin, Adab dan Humaniora, Universitas Islam Negeri Salatiga. Daryono, Yono dkk. 2008. Tegal Stad: Evolusi Sebuah Kota. Tegal: Kantor Informasi dan Humas Kota Tegal. Faidin. 2020. "Analisis Tinjauan Historiografi Dalam Buku Peristiwa Tiga Daerah". Jurnal PIPA: Pendidikan Ilmu Pengetahuan Alam, 1(2): 31. Heryati. 2017. Pengantar Ilmu Sejarah. Palembang: Universitas Muhammadiyah Palembang. http://repository.um-palembang.ac.id/id/eprint/16087/ Info Tegal. 2020. "Tak banyak yang tahu bahwa tahun 1927 ada 16 orang Tegal diasingkan ke Boven Digoel, Papua". Facebook. https://www.facebook.com/photo/?fbid=3656963921037198&set=a.138760689524223 Kartodirdjo, Sartono. 1993. Pendekatan Ilmu Sosial Dalam Metodologi Sejarah. Jakarta: Gramedia Pustaka Utama. Kuntowijoyo. 1955. Pengantar Ilmu Sejarah. Yogyakarta: Bentang Pustaka. Lucas, Anton E. Pengantar Sartono Kartodirdjoo. 1989. Peristiwa Tiga Daerah; Revolusi Dalam Revolusi. Jakarta: Pustaka Utama Grafiti. Mokh. Mukhson. 1973. "Sekelumit tentang Peristiwa Gerakan Tiga Daerah, Naskah Pribadi". Muhammad Nuh. "Arsip Catatan Tertulis Jawaban Semdam tahun 1959". Samsudin, Mayjen. 2004. Mengapa G30S/PKI Gagal?: (Suatu Analisis). Jakarta: Yayasan Obor Indonesia. Soedjono. 1974. "Gerakan Tiga Daerah, Naskah Pribadi". Suryomihardjo, Abdurrahman. 1961. Peristiwa Tiga Daerah Suatu Interpretasi Sejarah: Revolusi Sosial Menyambut Proklamasi Kemerdekaan. Prisma Edisi No. 8, Jakarta: LP3ES. Tasrif. "Surat Kabar Berita Indonesia: Soeara Perdjoeangan Terbitan 9 November 1945". Wiyono dkk. 1991. Sejarah Revolusi Kemerdekaan (1945-1949) Daerah Jawwa Tengah. Jakarta: Departemen Pendidikan dan Kebudayaan.